The Role and Influence of Parents In Forming Muslim Intellectuals Following Ahlussunnah Wal Jama’ah (Case Study at The At-Tahdzib Boarding School) - Taufiqurrohman, Taufiqurrohman; Jasminto, Jasminto (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to explore the role and influence of caregivers in shaping Muslim intellectuals who follow Ahlussunnah wal Jamaah at the Attahdzib Islamic Boarding School. The main focus of this study is to understand the role of Father Kyai Ahmad Masruh as a caregiver of the Islamic boarding school in guiding students to develop an understanding of religion in accordance with the teachings of Ahlussunnah wal Jamaah, and how he becomes a role model who provides examples in everyday life. The research method used is qualitative with a case study approach. Data collection was carried out through observation, interviews, and documentation conducted at the Attahdzib Islamic Boarding School. There are two focuses in this study, namely: (1) What is the role of caregivers in teaching the aqidah of Ahlussunnah wal Jamaah at the Attahdzib Islamic Boarding School? and (2) What is the role and influence of caregivers in shaping Muslim intellectuals who follow Ahlussunnah wal Jamaah at the Attahdzib Islamic Boarding School? The results of the study indicate that Father Kyai Ahmad Masruh has a very important role in forming quality Muslim intellectuals, by teaching and exemplifying the teachings of Ahlussunnah wal Jamaah both in words and deeds. In addition, the material taught through the yellow book in this Islamic boarding school is also in line with the teachings of Ahlussunnah wal Jamaah, thus forming students who are not only intelligent in religious knowledge but also have noble morals. This study is expected to contribute to the development of Islamic boarding school education and enrich studies on the role of caregivers in forming the character of Muslim intellectuals based on the teachings of Ahlussunnah wal Jamaah.